2017
DOI: 10.5120/ijca2017914643
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for Machine Learning based Spatial Data Analysis: Research Directions

Abstract: Today, machine learning techniques play a significant role in data analysis, predictive modeling and visualization. The main aim of the machine learning algorithms is that they first learn from the empirical data and can be utilized in cases for which the modeled phenomenon is hidden or not yet described. Several significant techniques like -Artificial Neural Network, Support Vector Regression, k-Nearest Neighbour, Bayesian Classifiers and Decision Trees are developed in past years to acheive this task. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The important thing of this paradigm is the unconventional structure of the information processing systems. They can give reasonable answers for issues, which are for the most part described by non-linear ties, high dimensional, noisy, complex, loose, and imperfect or mistake inclined sensor information [20]. Similar to biological neural networks, it is a system composed of many interconnected neurons (nerve cells), which receive process and transfer information.…”
Section: Artificial Neural Network In Context Of Spatial Data Miningmentioning
confidence: 99%
“…The important thing of this paradigm is the unconventional structure of the information processing systems. They can give reasonable answers for issues, which are for the most part described by non-linear ties, high dimensional, noisy, complex, loose, and imperfect or mistake inclined sensor information [20]. Similar to biological neural networks, it is a system composed of many interconnected neurons (nerve cells), which receive process and transfer information.…”
Section: Artificial Neural Network In Context Of Spatial Data Miningmentioning
confidence: 99%
“…Supervised ML algorithms can be trained using data to create a model for the prediction of specific phenomena [24]. For example, Generalized Linear Models (GLM) and Generalized Additive Models (GAM) were reported by [13] and [25], respectively, where improved landslide susceptibility modelling was obtained by taking advantage of the linear and nonlinear relationships of the predictor variables.…”
Section: Related Studiesmentioning
confidence: 99%
“…Shirzadi et al research [22] has also demonstrated that less complex ML can still be used in a variety of applications despite the deep learning trend. Data can be used to train supervised ML algorithms to build models for the prediction of particular phenomena [38] as described by [39]. In another study [40], In addition to random forest and CART, boosted regression tree (BRT) and GLM were employed to identify areas at risk for landslides (classification and regression tree).…”
Section: Introductionmentioning
confidence: 99%